2003
DOI: 10.1038/sj.onc.1206200
|View full text |Cite
|
Sign up to set email alerts
|

β-Hydroxyisovalerylshikonin induces apoptosis in human leukemia cells by inhibiting the activity of a polo-like kinase 1 (PLK1)

Abstract: b-Hydroxyisovalerylshikonin (b-HIVS), which was isolated from the plant, Lithospermum radix, induces apoptosis in various lines of human tumor cells. To identify genes involved in b-HIVS-induced apoptotic process, we performed cDNA array analysis and found that b-HIVS suppresses the expression of the gene for a polo-like kinase 1 (PLK1) that is involved in control of the cell cycle. When U937 and HL60 cells were treated with 10 À6 m b-HIVS for 0.5 h, both the amount of PLK1 itself and the kinase activity of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
32
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(38 citation statements)
references
References 64 publications
6
32
0
Order By: Relevance
“…9A (left panel), the extent of the tyrosine phosphorylation of proteins in DMS114 cells was clearly reduced after treatment of the cells with ␤-HIVS and the expression of both TRAP1 and PLK1 was suppressed in a dose-dependent manner. These results were consistent with our previous finding that the expression of PLK1 is suppressed, via inhibition of tyrosine kinase activity, by ␤-HIVS (14). The results in Fig.…”
Section: Expression Of Bcl-2 Inhibits Both the Release Of Cytochrome supporting
confidence: 83%
See 3 more Smart Citations
“…9A (left panel), the extent of the tyrosine phosphorylation of proteins in DMS114 cells was clearly reduced after treatment of the cells with ␤-HIVS and the expression of both TRAP1 and PLK1 was suppressed in a dose-dependent manner. These results were consistent with our previous finding that the expression of PLK1 is suppressed, via inhibition of tyrosine kinase activity, by ␤-HIVS (14). The results in Fig.…”
Section: Expression Of Bcl-2 Inhibits Both the Release Of Cytochrome supporting
confidence: 83%
“…We also showed that the effect of ␤-HIVS on PLK1 activity occurs upstream of mitochondria (14). Mitochondria play an important role in the regulation of apoptosis by releasing apoptogenic molecules that include cytochrome c (50 -52).…”
Section: Suppression Of Expression Of the Gene For Trap1 In Humanmentioning
confidence: 91%
See 2 more Smart Citations
“…Expression of the Plk1 gene was significantly suppressed by b-hydroxyisovalerylshikonin (b-HIVS) in U937 and HL60 cells (Masuda et al, 2003). Treatment with Plk1-specific antisense ODNs sensitized K562 cells to b-HIVS-induced apoptosis, indicating that suppression of the expression and activity of Plk1 by b-HIVS is involved in apoptosis (Masuda et al, 2003).…”
Section: Inhibition Of Plk1mentioning
confidence: 99%